2010
DOI: 10.3109/14992027.2010.492401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing pulse rate on profile parameters of perceptual thresholds and loudness comfort levels and relation to ECAP thresholds in recipients of the Nucleus CI24RE device

Abstract: The Nucleus CI24RE ‘Freedom' device offers higher stimulation rates and lower noise levels in action potential measurements (ECAPs) than previous devices. A study including ten European implant teams showed that the effect of changes in rate from 250 to 3500 pulses per second on tilt and curvature of the T and C profiles is insignificant. When changing rate one may change the levels at all electrodes by the same amount. Using an automated procedure ECAPs could be measured quickly and reliably at a noise level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
6
8
1
Order By: Relevance
“…This is obviously less than the 20 dB DR obtained when T-levels are set at 10% of the M-levels, which is the default setting in SoundWave, the manufacturer's fitting software. The 9-to 14-dB electrical DR is in line with the data reported by Wesarg et al [2010] for Nucleus cochlear implant recipients. In previous studies, even lower DRs of around 8 dB were described [Pfingst and Xu, 2005].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is obviously less than the 20 dB DR obtained when T-levels are set at 10% of the M-levels, which is the default setting in SoundWave, the manufacturer's fitting software. The 9-to 14-dB electrical DR is in line with the data reported by Wesarg et al [2010] for Nucleus cochlear implant recipients. In previous studies, even lower DRs of around 8 dB were described [Pfingst and Xu, 2005].…”
Section: Discussionsupporting
confidence: 90%
“…Smoorenburg [2007] reported increases in T-and M-levels for both adults and children. In contrast to Smoorenburg [2007], Walravens et al [2006], Hughes et al [2001] and Wesarg et al [2010] showed stable T-levels in adults after initial fitting. In children, Hughes et al [2001] showed that T-and M-levels continued to increase months after implantation and first fitting.…”
contrasting
confidence: 64%
See 3 more Smart Citations